Factors influencing sleeping pattern of infants - Yılmaz, Gonca; Gürakan, Berkan; Çakır, Banu; Tezcan, Sabahat (The Turkish Journal of Pediatrics, 2002)
Many families apply to pediatricians with complaints of sleep problems of their infants. It is very important to inform families about the sleep pattern of infants and factors influencing it, and to answer their questions about infantile sleep. A questionnaire was given to 165 families to elucidate the factors influencing continuous sleep pattern of the baby. Our study demonstrated that 50% of four-month-old and 96% of nine-month-old infants acquired continuous sleep pattern. Our figures were compatible and even higher than those in the literature. None of the factors studied has an independent effect on infantile continuous sleep pattern in multifactorial analysis. Early weaning does not facilitate acquisition of continuous sleep pattern by the baby. This will help to support prolonged breast-feeding. It may be advisable not to keep children beside their mother during sleep for a long period of time. Care of the children by the maternal grandmother may facilitate their acquisition of continuous sleep pattern.